2021
DOI: 10.1371/journal.pone.0250880
|View full text |Cite
|
Sign up to set email alerts
|

The decomposition process and nutrient release of invasive plant litter regulated by nutrient enrichment and water level change

Abstract: Wetlands are vulnerable to plant invasions and the decomposition of invasive plant litter could make impacts on the ecosystem services of wetlands including nutrient cycle and carbon sequestration. However, few studies have explored the effects of nutrient enrichment and water level change on the decomposition of invasive plant litter. In this study, we conducted a control experiment using the litterbag method to compare the decomposition rates and nutrient release in the litter of an invasive plant Alternanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…t 50 and t 95 for different components ranged from 50 to 327 and 216-1,414 days, respectively (Table 4) as it depends on various factors such as biochemistry of components, behavior of soil and edaphic factors. The higher t 50 and t 95 reported by Bohara et al (2019) were 456-569 and 3,289-4,125, respectively, in shrubland of Taihang Mountain, North China; Yang et al (2021) reported 880-1,529 for t 50 and 3,938-6,563 days for t 95 and Huang et al (2011) reported 324-511 days for t 50 and 1,405-2,119 days for t 95 . Caliman et al (2020) reported 84-284 days for t 50 days and 372-1,230 days for t 95 for multipurpose trees in Central India, which was lower than reported in the present study.…”
Section: Decomposition and Mass Lossmentioning
confidence: 86%
“…t 50 and t 95 for different components ranged from 50 to 327 and 216-1,414 days, respectively (Table 4) as it depends on various factors such as biochemistry of components, behavior of soil and edaphic factors. The higher t 50 and t 95 reported by Bohara et al (2019) were 456-569 and 3,289-4,125, respectively, in shrubland of Taihang Mountain, North China; Yang et al (2021) reported 880-1,529 for t 50 and 3,938-6,563 days for t 95 and Huang et al (2011) reported 324-511 days for t 50 and 1,405-2,119 days for t 95 . Caliman et al (2020) reported 84-284 days for t 50 days and 372-1,230 days for t 95 for multipurpose trees in Central India, which was lower than reported in the present study.…”
Section: Decomposition and Mass Lossmentioning
confidence: 86%
“…The trend showed that manure treatment produced a higher yield at both vegetative and generative stages (Table 9). This could be because the C/N ratio of manure was released for plant growth (Yang et al, 2021). Interestingly, available K positively correlated with all agronomic parameters, while a negative correlation was found between CH4 emission and agronomic parameters in both organic and conventional farming systems (Table 9).…”
Section: Discussionmentioning
confidence: 97%
“…Especially in the case of small and resource poor farmers, with reduced usage of machinery cost (<65.52%) under CA, farmers spend less (14.46%) on different cultivation practices, increasing their net returns as compared to conventional agriculture practices [86,87]. In sub-Saharan Africa, scientific studies revealed that with systematic use of practices such as no-tillage, residue retention and crop rotation the costs of cultivating maize or soybean were reduced (20-29%) and the net returns, the benefit-cost ratio increased to a greater extent [88][89][90][91][92][93][94][95][96][97][98]. A similar impact of less soil disturbing practices such as permanent beds and zero tillage was obtained on net returns or profitability of maize-chickpea rotation in India (28.8% and 24% respectively) [99][100][101][102][103].…”
Section: Economics Under Ca Systems: No Regret Optionsmentioning
confidence: 99%